Upaya Meningkatkan Keterampilan Berbicara Di Depan Umum - Riris Nurkholidah Rambe; Andini Syahfitri; Aini Humayroh; Nadila Alfina; Putri Azkia; Tania Dwi Rianti (Lembaga Pengembangan Kinerja Dosen, 2023)
Speaking in general can be interpreted as conveying one's intentions (ideas, thoughts, thoughts, or feelings) to others by using spoken language so that these intentions can be understood by others. The development of speaking is the stage where the child has begun to be able to convey the message he wants. in the form of sound sequences in the form of two or three words. Good language development, especially in speaking Makes children able to express their thoughts and feelings intelligently according to the context and situation when he is speaking. The goal is for students to be involved realistically rather than just practicing linguistic material. In the learning process at school, students' speaking skills still need to be guided, especially with good learning modeling from the teacher. And speaking skills are skills possessed by a person to convey ideas, feelings, and ideas to other people orally. The method used in this study uses the library research method or approach, library research or literature. In an effort to develop public speaking skills, the teacher can provide motivation so that students can improve their communication skills in speaking.